Behavioural response of a whale shark during the passage of a typhoon. Issue 6 (16th September 2021) - Nakamura, Itsumi; Tsuchida, Hiroyuki; Tone, Kazuki; Komeyama, Kazuyoshi; Sasaki, Akira; Kawabe, Ryo
Abstract: During a behavioural survey of a tagged whale shark ( Rhincodon typus ) conducted in 2019 in the waters off Kagoshima, Japan, a typhoon passed close to the area under surveillance. As the typhoon approached, monitoring of the shark's movements indicated that it dived to depths of up to 90 m, and during this period, the authors recorded the effects of the typhoon‐induced waves. They also detected changes in the vertical thermal structure of the waters, possibly due to the disturbance caused by the typhoon.